Ertl and Non-Ertl amputees exhibit functional biomechanical differences during the sit-to-stand task. (May 2017) - Ferris, Abbie E.; Christiansen, Cory L.; Heise, Gary D.; Hahn, David; Smith, Jeremy D.
Abstract: Background: People with transtibial amputation stand ~ 50 times/day. There are two general approaches to transtibial amputation: 1) distal tibia and fibula union using a "bone-bridge" (Ertl), 2) non-union of the tibia and fibula (Non-Ertl). The Ertl technique may improve functional outcomes by increasing the end-bearing ability of the residual limb. We hypothesized individuals with an Ertl would perform a five-time sit-to-stand task faster through greater involvement/end-bearing of the affected limb. Methods: Ertl (n = 11) and Non-Ertl (n = 7) participants sat on a chair with each foot on separate force plates and performed the five-time sit-to-stand task. A symmetry index (intact vs affected limbs) was calculated using peak ground reaction forces. Findings: The Ertl group performed the task significantly faster (9.33 s (2.66) vs 13.27 (2.83) s). Symmetry index (23.33 (23.83)% Ertl, 36.53 (13.51)% Non-Ertl) indicated the intact limb for both groups produced more force than the affected limb. Ertl affected limb peak ground reaction forces were significantly larger than the Non-Ertl affected limb. Peak knee power and net work of the affected limb were smaller than their respective intact limb for both groups. The Ertl intact limb produced significantly greater peak knee power and net work than the Non-Ertl intact knee. Interpretation: Although loading asymmetries existed between the intact and affected limb of both groups, the Ertl group performed the task ~ 30% faster. This was driven by greater power and work production of the Ertl intact limb knee. Our results suggest that functional differences exist between the procedures. Highlights: Functional differences between Ertl and Non-Ertl amputations are unknown. The Ertl group performed the sit-to-stand task ~ 30% faster. Ertl amputated limb peak ground reaction forces were significantly larger. Our results suggest that functional differences exist between the procedures.